Current aortic endografts for the treatment of abdominal aortic aneurysms. (3rd May 2016) - Colvard, Benjamin; Georg, Yannick; Chakfe, Nabil; Swanstrom, Lee
ABSTRACT: Endovascular Aneurysm Repair is a widely adopted method of treatment for patients with abdominal aortic aneurysms. The minimally invasive approach offered with EVAR has become popular not only among physicians and patients, but in the medical device industry as well. Over the past 25 years the global market for aortic endografts has increased rapidly, resulting in a wide range of devices from various companies. Currently, there are seven endografts approved by the FDA for the treatment of abdominal aortic aneurysms. These devices offer a wide range of designs intended to increase inclusion criteria while decreasing technical complications such as endoleak and migration. Despite advances in device design, secondary interventions and follow-up requirements remain a significant issue. New devices are currently being studied in the U.S. and abroad and may significantly reduce complications and secondary interventions.